HUBUNGAN KECEPATAN LARI DAN KOORDINASI MATA-KAKI DENGAN HASIL DRIBLE PADA TIM SEPAK BOLA SMK TELKOM PEKANBARU - Alya mardevis Mardevis; Ni Putu Nita Wijayanti Nita Wijayanti; Slamet ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The problem of this research begin from observation by writer find out in field and the writer also do some interview to couch of football in SMK Telkom Pekanbaru, the name Mr. Indra irwansyah. When i saw the Failures in doing drible, lack of running speed and eye-foot coordination when do drible then produce the minimum drible. The purpose of the research is to know relationship running speed and eye-foot coordination with drible result in the football team SMK TELKOM Pekanbaru. Sample of this research is sixteen player and one opulation. Because total of population lower taking, Sample in this research is the over all(total sampling).To get data then in this research using running speed test 40 yard for running speed. Test goal kick catching the ball diameter 65cm, 1,25m high goals and objectives with the start line distance of 2m to eye-foot coordination. And test drible buy using stopwatch and kun as much as 6 pieces which point to the direction and limiting the time of drible, the distance betwen kun 5m, and the distance between the starting line by kun 5m to the drible. The result of data analyse with correlation product momen. Based on data analyse from correlation X1 with Y as big as r count=0,52 > r table=0,497 and X2 with Y as big as r count=0,73 > r table=0,497, while X1, X2 with Y as big as R count=0,65 > r table=0,497. From this data analyse than over all there are relatinship, and than Ho rejected and Ha be accepted. Its means there are relationship running speed and eye-foot coordination with drible result on the football team SMK TELKOM Pekanbaru.Where the provision of a correlation or in the relationship between one variable with another variable is determined from r count > r table. Keyword: running speed, eye-foot coordination, and drible